Pengaruh Pengelolaan Tanaman Terpadu terhadap Efisiensi Teknis Kedelai - Apriliana, Herlinda; Winandi, Ratna; Pambudy, Rachmat (Jurnal Ilmu Pertanian Indonesia, 2020)
This study aims to analyze the impact of Integrated Crop Management (PTT) on technical efficiency. PTT is a government program undertaken in an effort to increase soybean productivity. PTT program is done by applying technology in the use of input management of soybean production. The method used in this research is using Stochastic Frontier (SFA) method with Cobb-Douglas production function. The location of this research is in Nganjuk District, East Java. Based on the results obtained that soybean farmers in Nganjuk district on average have been technically efficient. However, the soybean farmers program that PTT has a higher technical value compared to soybean farmers who do not follow PTT. The production input factors that affect production are superior seed, labor, fertilizer, and pesticide. While socio-economic factors are extension, landowner status, and number of family dependents.Keywords: PTT, soybean, stochastic frontier, technical efficiency